Quantitative and Microstructural Changes of the Blood-Nerve Barrier in Peripheral Neuropathy - Reinhold, Ann Kristin; Schwabe, Joachim; Lux, Thomas J.; Salvador, Ellaine; Rittner, Heike L. (Frontiers in Neuroscience, 2018)
Peripheral neuropathy is accompanied by changes in the neuronal environment. The blood-nerve barrier (BNB) is crucial in protecting the neural homeostasis: Tight junctions (TJ) seal paracellular spaces and thus prevent external stimuli from entering. In different models of neuropathic pain, the BNB is impaired, thus contributing to local damage, immune cells invasion and, ultimately, the development of neuropathy with its symptoms. In this study, we examined changes in expression and microstructural localization of two key tight junction proteins (TJP), claudin-1 and the cytoplasmic anchoring ZO-1, in the sciatic nerve of mice subjected to chronic constriction injury (CCI). Via qPCR and analysis of fluorescence immunohistochemistry, a marked downregulation of mRNA as well as decreased fluorescence intensity were observed in the nerve for both proteins. Moreover, a distinct zig-zag structure for both proteins located at cell-cell contacts, indicative of the localization of TJs, was observed in the perineurial compartment of sham-operated animals. This microstructural location in cell-cell-contacts was lost in neuropathy as semiquantified via computational analysis, based on a novel algorithm. In summary, we provide evidence that peripheral neuropathy is not only associated with decrease in relevant TJPs but also exhibits alterations in TJP arrangement and loss in barrier tightness, presumably due to internalization. Specifically, semiquantification of TJP in cell-cell-contacts of microcompartments could be used in the future for routine clinical samples of patients with neuropathy.